Epidemiological Manifestations of Purulent Bacterial Meningitis in the Russian Federation - M. A. Davydenko; N. S. Churilova; I. S. Koroleva (Эпидемиология и вакцинопрофилактика)
Relevance. Although meningitis is largely preventable, it still causes hundreds of thousands of deaths worldwide each year. Significant progress has been made in reducing meningitis mortality over the past three decades. The incidence of meningococcal, pneumococcal, and Haemophilus influenzae type b meningitis has declined due to the introduction of vaccination into national immunization programs in countries around the world. Aim. To determine the epidemiological manifestations of purulent bacterial meningitis (GBM) in the Russian Federation (RF) in 2023. Materials and methods. An in-depth personalized system for recording purulent bacterial meningitis cases has been established at the Russian Reference Center for Bacterial Meningitis Monitoring. Since 2010, all territories of the Russian Federation have been included in the monitoring system. In 2023, the Reference Center received information on 1,837 cases of purulent bacterial meningitis. The paper uses a descriptive and evaluative epidemiological method: retrospective analysis. Results and discussion. The incidence of GBM in the Russian Federation over a fourteen-year observation period has a downward trend. Meningococcus, pneumococcus and Haemophilus influenzae are the causes of 85% of GBM cases in the Russian Federation, while the infections they cause are potentially vaccine-preventable. Meningococcus continues to occupy a leading position in the etiology of GBM in the Russian Federation, causing 50% of all laboratory-confirmed cases. Despite a slight decrease in the incidence of meningococcal infection in 2023, its increase in the age group at risk, children under 5 years of age, by 39% was noted. In the serogroup characteristics of meningococcus, for the first time in the studied period, the predominance of meningococcus serogroup W was revealed. In 2023, the highest mortality rate from meningococcal infection was noted – 21%. The incidence rate of pneumococcal meningitis in the age group at risk, children under 5 years old, increased to 28% in 2023, and categories of adults are defined as risk groups for mortality. The incidence of meningitis caused by Haemophilus influenzae among children under 5 years old decreased by 44%, and all cases of death, with the exception of one, were noted in this age group. Conclusion. The data obtained make it possible to track the etiology of GBM, age groups and risk areas, which can serve as a basis for developing tactics to combat the disease with priority use of vaccines.